{gamma}-Protocadherins, presenilin-mediated release of C-terminal fragment promotes locus expression - Hambsch, Boris; Grinevich, Valery; Seeburg, Peter H; Schwarz, Martin K (The Journal of biological chemistry, 2005)
gamma-Protocadherins (gamma-pcdhs) are type I membrane-spanning glycoproteins, widely expressed in the mammal and required for survival. These cell adhesion molecules are expressed from a complex locus comprising 22 functional variable exons arranged in tandem, each encoding extracellular, transmembrane and intracellular sequence, and three exons for an invariant C-terminal domain (gamma-ICD). However, the signaling mechanisms that lie downstream of gamma-pcdhs have not been elucidated. Here we report that gamma-pcdhs are subject to presenilin-dependent intramembrane cleavage (PS-IP), accompanied by shedding of the extracellular domain. The cleaved intracellular domain (gamma-ICD) translocates to the cell nucleus and was detected in subsets of cortical neurons. Notably, gene-targeted mice lacking functional gamma-ICD sequence showed severely reduced gamma-pcdh mRNA levels and neonatal lethality. Most importantly, inhibition of gamma-secretase decreased gamma-pcdh locus expression. Luciferase reporter assays demonstrated that gamma-pcdh promoter activity is increased by gamma-ICD. These results reveal an intracellular signaling mechanism for gamma-pcdhs and identify a novel vital target for the gamma-secretase complex.